A Study on the Enamel Erosion Caused by Energy Drinks - Jeong, Moon-Jin; Jeong, Soon-Jeong; Son, Jung-Hui; Chung, Sung-Kyun; Kim, A-Reum; Kang, Eun-Ju; Kim, Eun-Ju; Kim, Hye-In; Jang, Ko-Eun; Cho, Min-Hee; Cheon, Ye-Ji; Choi, Hyo-Jung; et al. (Chiwisaeng gwahakoeji, 2014)
To find out the effect of commercially available energy drinks on tooth enamel erosion, analyzed pH, buffering capacity, and the content of some of the inorganic components selecting 4 energy drinks that has high affinity of the products currently being sold. In addition, by observing the degree of erosion before and after immersion in energy drink by surface microhardness and scanning electron microscope (SEM) the results were as follows: Acidity of energy drink ʻBurn Intenseʼ was the lowest as 2.78±0.01 highest on distilled water as 6.475±0.01. ʻBurn Intenseʼ buffering capacity was 3.48±0.155 at pH 5.5, 1.88±0.15 at pH 7.0 which is the highest, and ʻHot6ʼ was 1.71±0.37, 1.23±0.35 on each of it showing the lowest points. Ca content on energy drink was the highest at ʻVolt Energyʼ as (77.21±2.70 mg/kg), the lowest at ʻHot6ʼ as (0.98±0.05 mg/kg). P content was the highest on ʻHot6ʼ(1.34±0.05 mg/kg) and detected at ʻRed Bullʼ. Enamel surface hardness variation of the energy drinks before and after immersion showed rapid decrease at ʻRed Bullʼ (66.65±35.60), and ʻVolt Energyʼ (61.96±31.42), ʻBurn Intenseʼ (58.53±24.84), ʻHot6ʼ (53.99±60.26) was in order. Distilled water, the control group, showed significant difference with the experimental group (p＜0.05). But there was no significant difference between energy drinks. At SEM observation and analysis, ʻBurn Intenseʼ was the most severe demineralization, ʻVolt Energyʼ, ʻHot6ʼ, ʻRed Bullʼ, distilled water was in order. In the above results, taken together there were no statistically differences between energy drinks but significant difference in comparison with distilled water. In addition, at SEM observation and analysis all energy drink caused dental erosion, especially ʻBurn Intenseʼ, has the lowest acidity, was serious. Thus, it is believed to provide a variety of oral health education and information about energy drinks that can affect the erosion of the teeth so public have the right to be recognized and reasonable dental care. KCI Citation Count: 5